Regulatory approaches to managing skilled migration: Indonesian nurses in Japan. (June 2016) - Ford, Michele; Kawashima, Kumiko
This article examines the Japan–Indonesia Economic Partnership Agreement, an agreement that has allowed Japan to supplement its local healthcare workforce while continuing to sidestep the thorny issue of labour and immigration policy reform and Indonesia to increase its skilled workers' access to the Japanese labour market at a time when it was making a concerted effort to reorient migrant labour flows away from informal sector occupations. Despite the programme's many problems, it has contributed to the use of trade agreements as a mechanism for regulating labour migration, and so to the normalisation of migrant labour as a tradable commodity rather than a discrete area of policy-making, with all the attendant risks that normalisation brings.